(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This paper focuses on the problem of reading comprehension that was identified during the collection of documents. Therefore, we consider it relevant to address this issue, and give visibility to the importance of reading comprehension, since Maira Arrieta (2022) maintains that "students require a didactic strategy capable of arousing interest in the understanding and interpretation of texts, focusing on cognitive and linguistic skills, which determines the semantic and, at the same time, syntactic information developed in good reading" (p. 3). Consequently, new methodologies have emerged that seek to use games for the teaching-learning process, promoting reading comprehension. In addition, a study has been carried out of the different collected texts that share research on how the use of gamification in classrooms contributes to current education and makes learning reading comprehension a significant process for students. students.